2012
DOI: 10.1089/neu.2012.2471
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Effects of Nicotinamide and Progesterone on Functional Recovery of Cognitive Behavior following Cortical Contusion Injury in the Rat

Abstract: The primary goal of this study was to compare clinically relevant doses of progesterone and nicotinamide within the same injury model. Progesterone has been shown to reduce edema and inflammation and improve functional outcomes following brain injury. Nicotinamide has also been shown to be an effective neuroprotective agent in a variety of neurological injury models. In the current study, nicotinamide was administered beginning 4 h post-cortical contusion injury (CCI) with a loading dose (75 mg/kg, i.p.) combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 36 publications
3
40
0
Order By: Relevance
“…The NAM treatment in this study either confirmed or was more beneficial than previous preclinical data in animal models of TBI. [3][4][5][6][7]9,[11][12][13]55 NAM treatment resulted in significant improvements in both of the fine motor assessments. In the forelimb asymmetry task, the NAM-treated animals performed similar to previous research.…”
Section: Figmentioning
confidence: 95%
See 4 more Smart Citations
“…The NAM treatment in this study either confirmed or was more beneficial than previous preclinical data in animal models of TBI. [3][4][5][6][7]9,[11][12][13]55 NAM treatment resulted in significant improvements in both of the fine motor assessments. In the forelimb asymmetry task, the NAM-treated animals performed similar to previous research.…”
Section: Figmentioning
confidence: 95%
“…The CCI model utilized in the present study was based on previous studies and was intended to produce a moderately severe injury. 8,9,12,41 Animals were anesthetized using a mixture of isoflurane (2-4%) and oxygen (0.8 L/m). When the animal became unresponsive (no ocular or pedal reflexes) the head was shaved and scrubbed with 70% alcohol followed by betadine and placed into a stereotaxic device.…”
Section: Surgerymentioning
confidence: 99%
See 3 more Smart Citations